Implementasi Jaringan Nirkabel BWA (Broadband Wireless Access) Menggunakan Wimax - Nanang Sadikin; Marliana Sari; Jumanta Jumanta (KILAT, 2019)
Broadband Wireless Access is new standard of Wireless LAN (WLAN) developed by IEEE which standard is 108.16.The significance of BWA is wide area coverage, more users and without Line of Sight in some situation. This research is using literature study and observation, design and build WLAN network using BWA Wimax. The goal is build wireless network between two offices separate by remote area until fifty kilometres. Summary of this research is two location can be connected using WiMAX Broadband Wireless Access (BWA).